Sentinel lymph node biopsy based on anatomical landmarks and locoregional mapping of inguinofemoral sentinel lymph nodes in women with vulval cancer: an operative technique - Fong Lien Kwong; Miski Scerif; Jason KW Yap (Taylor & Francis Group, 2023)
Inguinal lymph node involvement is the most robust predictor of mortality in vulval cancer and sentinel lymph node (SLN) biopsy is a safe diagnostic modality. We describe a technique based on anatomical landmarks. Our aims are (1) to describe the territorial mapping of SLNs, (2) to evaluate the associated complication rate vis-à-vis those reported in the literature, and (3) to assess its accuracy in detecting SLNs. Data from women who underwent groin SLN biopsies for vulval cancer at a single cancer centre were prospectively collected. All subjects met the GROINSS-V eligibility criteria. The location of the SLN relative to the saphenous vein was recorded. All women were followed up and early and late complications were recorded. The recurrence rate at the time of the census was calculated. A total of 71 groins in 44 women were included. The SLN was primarily located over Cloquet's node (85.2%). The incidence of early wound cellulitis and dehiscence were 2.8% and 11.3% while lymphocysts were present in 11.3% of groins. The negative nodal recurrence rate was 1.7%. Results showed that this reproducible technique allows access to 96.7% of SLNs, including both deep and superficial SLNs whilst minimising the need for extensive dissection and complications associated with overharvesting of lymph nodes.